TECHNOPRENEURSHIP DAN DROP-SHIPPING TINJAUANPERSPEKTIF RISIKO INVESTASI DAN PERSEDIAAN - Pane, Dian (JURNAL PERSPEKTIF BISNIS, 2013)
The purpose of this theoretical study is to examine the theoretical basis of Technopreneurship in drop-shipping which compared with the theory of traditional distribution channels as well as linkages with the theory of supply chain management and inventory investment risk perspective. Furthermore, an analysis of the number of the previous research and then be concluded that drop-shipping at level of e-tailer to be breakthrough in the distribution channel for its used in blackberry messenger applications encourage entrepreneurship desires even though with the limited capital. Ease of running business with a lower risk than conventional channels made the drop-shipping as an alternative business option based technology by using the smartphone.Keywords: Technopreneurship, Drop-shipping, E-Tailer, RisikoInvestasidanPersediaan, Blackberry Messenger.